PAIN MANAGEMENT IN THE CRITICAL ILL PATIENTS WITH MECHANICAL VENTILATOR: A Case Study - Chanif, - (Universitas Muhammadiyah Semarang, 2013)
Pain is the most common experiences and stressors in the critically ill patients, because many sources of pain are present in critical care settings, such as acute illness, surgery, trauma, invasive equipment, nursing and medical interventions. Poor treatment of acute pain may lead to the development of serious complications which may seriously impact the patient’s functioning, quality of life, and well being. The critical nurse must understand the mechanisms, assessment, and appropriate intervention in managing pain. This study aim to describe pain experience in critical ill patients with mechanical ventilator, identify the influencing factor for pain among critically ill patients with mechanical ventilator and evaluate the outcomes of evidence based interventions to reduce pain level among critically ill patient with mechanical ventilator. The author useddescriptive study for critical patients who administered mechanical ventilator and associated with a significant degree of pain. They were hospitalized in the Surgical Intensive Care Unit (SICU) and/or Surgical Respiratory Care Unit (SRCU). Moreover, selection criteria in this study include male or female patients who get mechanical ventilator, have either medical or surgical intervention and administered by using morphineinjection 10 mg/ml sig 3 mg or fentanyl injection sig 30 mcg IV q 3 hr IV as primary pain medication. Used both pharmacologic and nonpharmacologic pain management, the pain score decreased after intervention. Both pain management pharmacologic and nonpharmacologic can be used together in relieving pain. Usingpharmacologic alone may not fully relieve all aspects of pain. Keyword: Pain management, critical patients, mechanical ventilator